The scale of seed grinding at Lake Mungo. Issue 3 (27th August 2015) - Fullagar, Richard; Hayes, Elspeth; Stephenson, Birgitta; Field, Judith; Matheson, Carney; Stern, Nicola; Fitzsimmons, Kathryn E.
Abstract: Smith's Comment on our functional analysis of grinding stone fragments from Pleistocene contexts at Lake Mungo (Fullagar et al. 2015 ) draws attention to the low frequency of implements, uncertainties about functional interpretations and archaeological implications. He argues that Pleistocene seed exploitation at Lake Mungo was limited and probably not indicative of a seed grinding economy . We suggest that it is premature to speculate about the scale of seed grinding at Lake Mungo. We also use new data to address concerns raised about our methodology.